Cost Analysis of Caesarean Deliveries under INA-CBG’s Tariff System in Jogja Hospital, Indonesia - Ingenida Hadning; Zhafira As Syafa Putri Arditya (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: This study aimed to determine differences in the average real cost of caesarean section with INA-CBG’s. This study is the first to use the latest INA-CBG's in 2023, so it can provide an overview of the implementation of INA-CBG's in 2023. The finding has the potential to provide recommendations for improving reimbursement policies and can guide the development of more effective financing models for hospitals and patients, particularly regarding caesarean section costs. In light of the growing global demand for cost efficiency in healthcare, this study provides valuable insights into optimizing financing structures and resource allocation. Methods: The study uses a quantitative research approach with retrospective data from sectio caesarea patient medical records in Jogja Hospital during January-September 2023. A total of 30 patients were enrolled, and data were collected through total sampling. Ethical approval was obtained from the hospital director with number 56/KEPK/RSUD/IX/2023 Results: The study's primary outcome was that the average real cost of the Caesarea section is higher than the INA-CBG's 2023. Furthermore, it was found that there was a significant difference between the average real cost of sectio caesarea and INA-CBG's in class 1 INA-CBG's code O-6-10-I (sig.0.001), class 3 INA-CBG's code O-6-10-I (Sig.0.000) and class 3 INA-CBG's code O-6-10-II (Sig.0.028). There are results of insignificant differences in class 1 INA-CBG's code O-6-10-II (Sig.0.180), class 2 INA-CBG's code O-6-10-I (Sig.0.089), class 2 INA-CBG's code O-6-10-II (Sig.0.180). Conclusion: This study shows that there is a significant difference between the real cost and the INA-CBG's on the payment of patient claims for inpatient services at Jogja Hospital. Our study contributes to understanding healthcare reimbursement issues by the difference between the average cost of sectio caesarea and INA-CBG's. Future research should address the evaluation of the factors that can cause the difference between the cost of sectio caesarea and INA-CBG's 2023, which will ultimately advance knowledge in the field of international health.